The Aerodynamic Behavioral Study of Tandem Fan Wing Configuration - Du Siliang; Tang Zhengfei (International Journal of Aerospace Engineering)
The fan wing aircraft is a new concept based on a new principle, especially its wing which is based on a unique aerodynamic principle. A fan wing can simultaneously generate lift and thrust. In order to further improve its aerodynamic characteristics without changing its basic geometric parameters, two fan wings are installed along the longitudinal body, which is the composition of a tandem fan wing aircraft. Through numerical simulation, the lift and thrust of the fan wings were calculated with the distance, height, and installation angle of the front and rear fan wings changed, and the aerodynamic characteristic interaction rule between the front and rear fan wings was analyzed. In addition, the wind test model of a tandem fan wing was designed, and the results of the wind tunnel test and numerical calculation results were compared to verify the preliminary setup. The results show that at a certain height, distance, and installation angle, aerodynamic characteristics of a tandem fan wing have more advantages compared to the single fan wing. Therefore, the tandem fan wing aircraft’s advantages have good prospects for development and application.